Single organelle function and organization as estimated from Arabidopsis mitochondrial proteomics. (3rd November 2019) - Fuchs, Philippe; Rugen, Nils; Carrie, Chris; Elsässer, Marlene; Finkemeier, Iris; Giese, Jonas; Hildebrandt, Tatjana M.; Kühn, Kristina; Maurino, Veronica G.; Ruberti, Cristina; Schallenberg‐Rüdinger, Mareike; Steinbeck, Janina; et al.
Summary: Mitochondria host vital cellular functions, including oxidative phosphorylation and co‐factor biosynthesis, which are reflected in their proteome. At the cellular level plant mitochondria are organized into hundreds of discrete functional entities, which undergo dynamic fission and fusion. It is the individual organelle that operates in the living cell, yet biochemical and physiological assessments have exclusively focused on the characteristics of large populations of mitochondria. Here, we explore the protein composition of an individual average plant mitochondrion to deduce principles of functional and structural organisation. We perform proteomics on purified mitochondria from cultured heterotrophic Arabidopsis cells with intensity‐based absolute quantification and scale the dataset to the single organelle based on criteria that are justified by experimental evidence and theoretical considerations. We estimate that a total of 1.4 million protein molecules make up a single Arabidopsis mitochondrion on average. Copy numbers of the individual proteins span five orders of magnitude, ranging from >40 000 for Voltage‐Dependent Anion Channel 1 to sub‐stoichiometric copy numbers, i.e. less than a single copy per single mitochondrion, for several pentatricopeptide repeat proteins that modify mitochondrial transcripts. For our analysis, we consider the physical and chemical constraints of the single organelle and discuss prominent features of mitochondrial architecture, protein biogenesis, oxidative phosphorylation, metabolism, antioxidant defence, genome maintenance, gene expression, and dynamics. While assessing the limitations of our considerations, we exemplify how our understanding of biochemical function and structural organization of plant mitochondria can be connected in order to obtain global and specific insights into how organelles work. Significance Statement: We explore the structure and function of a single plant mitochondrion by scaling down a quantitative proteomic dataset of Arabidopsis cell culture mitochondria to calculate the copy numbers of individual protein species for a single organelle.